Multisystemic therapy versus management as usual in the treatment of adolescent antisocial behaviour (START): a pragmatic, randomised controlled, superiority trial. (February 2018) - Fonagy, Peter; Butler, Stephen; Cottrell, David; Scott, Stephen; Pilling, Stephen; Eisler, Ivan; Fuggle, Peter; Kraam, Abdullah; Byford, Sarah; Wason, James; Ellison, Rachel; Simes, Elizabeth; et al.
Summary: Background: Adolescent antisocial behaviour is a major health and social problem. Studies in the USA have shown that multisystemic therapy reduces such behaviour and the number of criminal offences committed by this group. However, findings outside the USA are equivocal. We aimed to assess the effectiveness and cost-effectiveness of multisystemic therapy versus management as usual in the treatment of adolescent antisocial behaviour. Methods: We did an 18 month, multisite, pragmatic, randomised controlled, superiority trial in England. Eligible participants aged 11–17 years with moderate-to-severe antisocial behaviour had at least three severity criteria indicating past difficulties across several settings and one of five general inclusion criteria for antisocial behaviour. We randomly assigned families (1:1) using stochastic minimisation, stratifying for treatment centre, sex, age at enrolment to study, and age at onset of antisocial behaviour, to receive either management as usual or 3–5 months of multisystemic therapy followed by management as usual. Research assistants and investigators were masked to treatment allocation; the participants could not be masked. The primary outcome was out-of-home placement at 18 months. The primary analysis included all randomised participants for whom data were available. This trial is registered, number ISRCTN77132214. Follow-up of the trial is still ongoing. Findings: Between Feb 4, 2010, and Sept 1, 2012, 1076 families were referred to nine multi-agency panels, 684 of whom were assigned to management as usual (n=342) or multisystemic therapy followed by management as usual (n=342). At 18 months, the proportion of participants in out-of-home placement was not significantly different between the groups (13% [43/340] in the multisystemic therapy group vs 11% [36/335] in the management-as-usual group; odds ratio 1·25, 95% CI 0·77–2·05; p=0·37). Interpretation: The findings do not support that multisystemic therapy should be used over management as usual as the intervention of choice for adolescents with moderate-to-severe antisocial behaviour. Funding: Department for Children, Schools and Families, Department of Health.